PSXI-37 Percentage of leaves and neutral detergent fiber content of the Mombaça grass cultivated in a crop-livestock-forest integration system in the Amazon region. (7th December 2018) - Lins, T; Reis, R; Balbinot, E; Melo, A; Ferraz, S; Padilha, F; Maciel, A; Sousa, F; Martins, G; Wachekowski, G
Abstract: This study aimed to evaluate the effect of shading caused by different orientations of ranks of eucalyptus (Eucalyptus spp.) on percentage of leaves (PL) and neutral detergent fiber (NDF) content of the Mombaça grass (Panicum maximum) cultivated in a crop-livestock-forest integration system, during the rainy season. The experiment was conducted at the Federal Institute of Rondônia, campus Colorado do Oeste-RO, Brazil (13°07'40''S, 60°29'07''W, 400m). The eucalyptus ranks were implanted in double rows, spaced 3x2m (between rows and between plants, respectively) and 26m between ranks. When Mombaça grass was sampled, the trees were, on average, 12m high. The experimental design was in randomized blocks, subdivided into plots (2x3) with three replications. The plots consisted of the two orientations planting of ranks (east-west and north-south), and the subplots were three parallel planting ranges between the ranks (ranges 1 and 3: 0 to 8, 6m in relation to the ranks; and range 2: 8.7 to 17.3m, located in the central part between the ranks). The statistical model used was: Yijk=μ+Pi+Sij+P*Sij+eijk, where: Yijk: observed value; μ: overall constant; Pi: effect of plot; Sij: effect of splitplot; P*Sij: effect of interaction and eijk: randomized error. There was no isolated effect of planting ranges on the percentage of leaves (P=0.131) and neutral detergent fiber (P=0.243). However, the Mombaça grass cultivated in the east-west direction presented lower percentage of leaves (P=0.015) and higher NDF content (P=0.011), with values of 85, 9% and 70, 14%, respectively. The cultivation in the north-south direction showed 95, 17% of PL, and 66, 95% of NDF content. It is concluded that in the Amazon region, rows of trees planted in the east-west direction increase the FND content of the forage due to reducing the percentage of leaves in detriment to the higher stem elongation due to the greater incidence of luminosity in the canopy of the forage.